Soil cover in vineyards modifies soil properties and nutritional status of the vines - Lehmann, Duane Heloisa; Cassol, Paulo Cezar; Sacomori, Wagner; Ferreira Teixeira, Ana Karolina; Mafra, Alvaro Luiz; Ernani, Paulo Roberto; Zalamena, Jovani (Revista de Ciências Agroveterinárias, 2016)
The cover crop intercropping in vineyards protects the soil from erosion and can be an alternative for controlling the growth of the vine. The aim of this study was to evaluate the changes in the soil’s chemical properties, leaf composition and branch growth of Cabernet Sauvignon vine caused by the cover crops in the vineyard. The study was carried in an experiment conducted from 2009 in the highlands of Santa Catarina state, where the soil and climatic conditions favor the excessive growth of the vine. The treatments consisted of three types of cover crops, two management and a control. The cover crops were annual, buckwheat (Fagopyrum esculentum) and ryegrass (Lolium multiflorum), the perennial fescue (Festuca arundinacea) and the native (spontaneous), while the managements were mowed with the crop residue in total area and, with its transfer from the row to the between row of the vine. Samples of leaves and soil were carried out in “veraison” and at end of grape maturation stages, respectively. The cover crops and its management in general did not change the soil pH, or the exchangeable content of Al, Ca and Mg, but the annual did increase the available P content in the 0-5 cm layer compared to the control. The perennial in general did increase the extractable K content compared to the control in the 5-10 and 10-15 cm layers, and compared to the annual and native crops in all of the soil layers. The perennial reduced the leaf contents of P and K when compared to other treatments, the Mg leaf content was compared to the annual and decreased the N leaf content and the mass of branches when compared to the control treatment.